Comprehensive toxicology. - McQueen, Charlene A., 1947- (Elsevier, 2010)
An explosive increase in the knowledge of the effects of chemical and physical agents on biological systems has led to an increased understanding of normal cellular functions and the consequences of their perturbations. The 14-volume Second Edition of Comprehensive Toxicology has been revised and updated to reflect new advances in toxicology research, including content by some of the leading researchers in the field. It remains the premier resource for toxicologists in academia, medicine, and corporations. Comprehensive Toxicology Second Edition provides a unique organ.